Onset of Microbial Influenced Corrosion (MIC) in stainless steel exposed to mixed species biofilms from equatorial seawater - Jogdeo, Prasanna (2018)
The understanding of microbial influenced corrosion (MIC) in aerobic mixed biofilms benefits from advanced microscopy and microbial ecology characterization of biofilms. Here, the onset of MIC in stainless steel coupons was studied in both natural and artificial seawater. Rapid selection of biofilm-forming microorganisms from natural seawater was observed for field experiments. Potential ennoblement was observed only in natural seawater. A seawater derived mixed microbial consortium enriched in artificial seawater was used to characterize the effect of several parameters on MIC. The concentration of organic carbon was the major determinant of MIC, while shaking speed and polishing played minor roles. The biofilm was preferentially formed at the grain boundaries. These results outline the need for MIC onset characterization with mixed microbial consortia to predict long-term corrosion behavior of stainless steel in seawater.